Ten-year fatal and non-fatal myocardial infarction incidence in elderly populations in Spain: the EPICARDIAN cohort study - Novella Blanca; López Isidro; Vega Saturio; Muñiz Javier; Reviriego Blanca; Alonso Margarita; Gabriel Rafael; Suárez Carmen; Rodríguez-Salvanés Francisco (BMC, 2009)
Abstract Background In Spain, more than 85% of coronary heart disease deaths occur in adults older than 65 years. However, coronary heart disease incidence and mortality in the Spanish elderly have been poorly described. The aim of this study is to estimate the ten-year incidence and mortality rates of myocardial infarction in a population-based large cohort of Spanish elders. Methods A population-based cohort of 3729 people older than 64 years old, free of previous myocardial infarction, was established in 1995 in three geographical areas of Spain. Any case of fatal and non-fatal myocardial infarction was investigated until December 2004 using the "cold pursuit method", previously used and validated by the the WHO-MONICA project. Results Men showed a significantly (p < 0.001) higher cumulative incidence of myocardial infarction (7.2%; 95%CI: 5.94-8.54) than women (3.8%; 95%CI: 3.06-4.74). Although cumulative incidence increased with age (p < 0.05), gender-differences tended to narrow. Adjusted incidence rates were higher in men (957 per 100 000 person-years) than in women (546 per 100 000 person-years) (p < 0.001) and increased with age (p < 0.001). The increase was progressive in women but not in men. Adjusted mortality rates were also higher in men than in women (p < 0.001), being three times higher in the age group of ≥ 85 years old than in the age group of 65-74 years old (p < 0.001). Conclusion Incidence of fatal and non-fatal myocardial infarction is high in the Spanish elderly population. Men show higher rates than women, but gender differences diminish with age.